Virtual Models for Real-World Learning: The Development and Evaluation of a Patient Simulator for Eye Disability Diagnosis - Muhammad Khuarizmi bin Mohd Rapi
Patient simulators have become an increasingly popular tool in medical education, providing a safe and realistic environment for students to practice clinical skills and decision-making. However, a notable gap exists in the realm of ophthalmology training, where the use of patient simulators is limited, especially for the diagnosis of eye disabilities. This study aims to address this critical gap by describing the development and evaluation of a patient simulator tailored for ophthalmology training, focusing on the diagnosis of eye disabilities. The simulator integrates real-world patient data and generates lifelike eye disability scenarios designed to challenge students' diagnostic skills. To achieve this, algorithm techniques are applied and evaluated to enhance the realism and effectiveness of the patient simulator for ophthalmology training. Additionally, user interface and user experience evaluation methods are designed and tested in optimizing the usability and confidentiality of the simulator, which incorporates different diagnostic tools and protects user information data. The research methodology encompasses the complete lifecycle of the simulator, including its development, the creation of several realistic eye disability scenarios, and the thorough evaluation of its effectiveness in enhancing student diagnostic capabilities. Results from this study reveal a significant improvement in students' ability to diagnose eye disabilities after utilizing the simulator. Furthermore, this research provides valuable insights into the intricacies and challenges associated with both the development and evaluation of patient simulators in the context of ophthalmology training. Beyond the immediate impact on educational practices, this study sheds light on potential avenues for future research in this area. By bridging the existing gap in ophthalmology training, the patient simulator introduced in this study holds the promise of being a valuable educational tool, offering students a realistic and engaging learning experience while simultaneously enhancing their diagnostic skills in the realm of eye disability diagnosis.